Nuclear softening mediated by Sun2 suppression delays mechanical stress-induced cellular senescence - Xianlin Yue; Jie Cui; Zewei Sun; Lei Liu; Ying Li; Liwei Shao; Qi Feng; Ziyue Wang; William S. Hambright; Yan Cui; Johnny Huard; Yanling Mu; et al. (Cell Death Discovery, 2023)
Abstract Nuclear decoupling and softening are the main cellular mechanisms to resist mechanical stress-induced nuclear/DNA damage, however, its molecular mechanisms remain much unknown. Our recent study of Hutchinson-Gilford progeria syndrome (HGPS) disease revealed the role of nuclear membrane protein Sun2 in mediating nuclear damages and cellular senescence in progeria cells. However, the potential role of Sun2 in mechanical stress-induced nuclear damage and its correlation with nuclear decoupling and softening is still not clear. By applying cyclic mechanical stretch to mesenchymal stromal cells (MSCs) of WT and Zmpset24−/− mice (Z24−/−, a model for HGPS), we observed much increased nuclear damage in Z24−/− MSCs, which also featured elevated Sun2 expression, RhoA activation, F-actin polymerization and nuclear stiffness, indicating the compromised nuclear decoupling capacity. Suppression of Sun2 with siRNA effectively reduced nuclear/DNA damages caused by mechanical stretch, which was mediated by increased nuclear decoupling and softening, and consequently improved nuclear deformability. Our results reveal that Sun2 is greatly involved in mediating mechanical stress-induced nuclear damage by regulating nuclear mechanical properties, and Sun2 suppression can be a novel therapeutic target for treating progeria aging or aging-related diseases.